RELIGIOUS VALUES IN NICHOLAS SPARKS’S A WALK TO REMEMBER - Viator Lumban Raja; Indah Suryani Silitonga (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This article discusses religious values in Nicholas Sparks’